Profil Bahasa-Bahasa di Papua - Willem Burung (Balai Bahasa Provinsi Papua, 2019)
Languages in Papua are conventionally divided into two main families: Austronesian and non-Austronesian or Papuan languages. This paper gives a brief account on the phonological and grammatical features of those languages by referring to the studies of Blust (2009), for the Austronesian languages, and Foley (1986, 2000), for the Papuan languages.